1998
DOI: 10.1111/j.1749-6632.1998.tb09903.x
|View full text |Cite
|
Sign up to set email alerts
|

The Universality of Bioenergetic Disease: Age‐associated Cellular Bioenergetic Degradation and Amelioration Therapy

Abstract: During the present century there has been a dramatic change in life expectancy in advanced societies, now exceeding 80 years. As distinct from life expectancy, life potential is said to be at least 120 years, so that the continuing increase in knowledge has the potential for further major changes in the survival of humans conceivably in the near future. This presentation will be concerned with one aspect of the development of biomedical advances related in part to a concept of an "age-related universality of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…Mitochondria are considered an important site of aging-associated processes (Harman, 1972;Linnane et al, 1998;Singh, 2004). Genes related to the electron transport chain (ETC) and ATP synthase have been examined using RNAi (Dillin et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria are considered an important site of aging-associated processes (Harman, 1972;Linnane et al, 1998;Singh, 2004). Genes related to the electron transport chain (ETC) and ATP synthase have been examined using RNAi (Dillin et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they suggested that circumventing the bioenergy depletion of cells from aging tissue by boosting the ability of cells to produce ATP would be beneficial in restoring cell function. To this end, they attempted to use redox therapy to reverse the lower levels of respiratory chain components with coenzyme Q 10 (48). Cells can survive in the absence of a functional mitochondrial respiratory chain provided they have a means to reoxidize NADH generated by glycolysis.…”
Section: Phenotypic and Functional Consequences Of Oxidative Injurymentioning
confidence: 99%
“…Accumulation of large deletions in mtDNA is associated with tissue damage in several human diseases, such as age-related disorders (Linnane et al 1998), liver cirrhosis (Mansouri et al 1997), and mitochondrial myopathy (Kim and Chi 1997).…”
Section: Introductionmentioning
confidence: 99%